2019
DOI: 10.33369/joall.v4i2.7681
|View full text |Cite
|
Sign up to set email alerts
|

Syntactical Error Analysis on Report Text

Abstract: This study aims at investigating and classifying the syntactical errors in the writing of report text made by 20 students of Department of English Literature of FIB-USU. Syntactical errors in writing made by EFL students are needed to be investigated by using the Error Analysis theory developed by Gass & Selinker in 2008 as it provides six appropriate investigation procedures, namely; collecting data, identifying errors, classifying errors, quantifying errors, analyzing errors and remediation.  Each of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…"Error considered to be evidence of learning strategies as it builds competence in the target language by regarding the rules of it" (Marina and Snuviskinie, 2005:275). The factors causing error are different grammar between L1 and L2, and lack of knowledge (Dinamika and Hanafiah, 2019). Therefore, it is obvious that learner makes errors in using target language "English" because they are still in the learning process.…”
Section: Literature Review Error Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…"Error considered to be evidence of learning strategies as it builds competence in the target language by regarding the rules of it" (Marina and Snuviskinie, 2005:275). The factors causing error are different grammar between L1 and L2, and lack of knowledge (Dinamika and Hanafiah, 2019). Therefore, it is obvious that learner makes errors in using target language "English" because they are still in the learning process.…”
Section: Literature Review Error Analysismentioning
confidence: 99%
“…It is shown by 17 error occurrences. In line, it was noticed that subject-verb do not agree in number (Marina and Snuviškienė, 2005;Dinamika and Hanafiah, 2019). Students made a wrong agreement i.e.…”
Section: Mechanical Errormentioning
confidence: 99%
“…By seeing these results, it can be inferred that the negative interference of learners' L1 doesn't significantly influence the errors they make in the undergraduate thesis abstracts, moreover, it is the lack of L2 knowledge does. In line with this finding, the research conducted by Dinamika and Hanafiah (2019) find that syntactical errors made by the students of the English Department of University of Sumatera Utara also had been affected by the L2 factors. In addition, Burhanuddin (2020:30) the errors in the questionnaire instruments which are written by students of the English Department of IAIN Pekalongan were caused by the students' incomplete L2 acquirement.…”
Section: Discussionmentioning
confidence: 57%
“…Getting the data from students' work, Kusumawardhani (2018) and Dinamika and Hanafiah (2019) found that morphology errors were quite dominating in students' work. Kusumawardhani (2018) found that a group of participants made derivational morphology errors in their English narrative compositions, such as in verbs, nouns, gerunds, and other forms.…”
Section: Introductionmentioning
confidence: 99%
“…Kusumawardhani (2018) found that a group of participants made derivational morphology errors in their English narrative compositions, such as in verbs, nouns, gerunds, and other forms. Moreover, Dinamika and Hanafiah (2019) found that even the students of the English Literature Department make many errors in their report text writings. Besides, the research findings revealed that the most errors were in the use of the article 'a/an/the'.…”
Section: Introductionmentioning
confidence: 99%